Dietary Lysine Levels Improved Antioxidant Capacity and Immunity via the TOR and p38 MAPK Signaling Pathways in Grass Carp, Ctenopharyngodon idellus Fry - Huang, Dongyu; Maulu, Sahya; Ren, Mingchun; Liang, Hualiang; Ge, Xianping; Ji, Ke; Yu, Heng (Frontiers in Immunology, 2021)
An 8-week rearing trial was designed to appraise the dietary lysine levels on intestinal antioxidant capacity and immunity of grass carp fry. Six practical diets were prepared with graded levels of lysine (1.44%, 1.79%, 1.97%, 2.44%, 2.56% and 2.87% dry matter), and these diets were fed to grass carp fry. The results showed that the activities of intestinal antioxidant factors including catalase and glutathione peroxidase were markedly improved by the 2.44% dietary lysine compared with the control diet (1.44% dietary lysine) (P < 0.05). In terms of antioxidants, compared with the control diet, the 2.44% diet markedly upregulated the mRNA expression levels of target of rapamycin, S6 kinase1 and nuclear factor erythroid 2-related factor 2 pathway-related antioxidant genes, containing catalase and glutathione peroxidase 1α (P < 0.05) and downregulated the mRNA levels of Kelch-like ECH-associated protein 1 (P > 0.05). The mRNA levels of 4E-binding protein 2 showed the opposite trend compared with those of target of rapamycin, and the minimum value was observed in the group of 1.97% dietary lysine (P < 0.05). In terms of immunity, compared with the 1.44% diet, the 2.44% diet markedly suppressed the intestinal p38 mitogen-activated protein kinase and interferon γ2 mRNA levels (P < 0.05). Moreover, nuclear factor-kappa B p65, tumor necrosis factor α, interleukin 6, interleukin 8 and interleukin 15 mRNA levels all exhibited the same trend as p38 mitogen-activated protein kinase and interferon γ2; however, the difference among all the lysine treatments groups was not significant (P > 0.05). The anti-inflammatory cytokines transforming growth factor β2 and interleukin 4/13B mRNA levels in the intestine were remarkably upregulated by high dietary lysine levels (2.56% and 2.87%) (P < 0.05), and when the dietary lysine level reached 2.44%, the interleukin 4/13A mRNA levels were strikingly increased (P < 0.05). Overall, the data suggested that 2.44% dietary lysine could strengthen the immune and antioxidant capacities of grass carp fry via activating the target of rapamycin (TOR) signaling pathway, and suppressing the p38 mitogen-activated protein kinase (p38 MAPK) signaling pathway, which then improve the survival rate.